Prostate cancer statistics, 2025 - Tyler B. Kratzer; Natalia Mazzitelli; Jessica Star; William L. Dahut; Ahmedin Jemal; Rebecca L. Siegel (CA: A Cancer Journal for Clinicians, 2025)
Abstract Prostate cancer is the most common cancer among men in the United States, and the incidence of advanced disease is increasing rapidly. This article provides an overview of prostate cancer occurrence using population‐based incidence and mortality data from the National Cancer Institute and the Centers for Disease Control and Prevention. Prostate cancer incidence trends have reversed from a decline of 6.4% per year during 2007 through 2014 to an increase of 3.0% annually during 2014 through 2021. The increasing trend is confined to distant‐stage disease in men younger than 55 years and to regional/distant‐stage disease in men aged 55–69 years but includes early stage disease in men aged 70 years and older. Over the past decade of data, distant‐stage disease has increased by 2.6% annually in men younger than 55 years, 6.0% annually in men aged 55–69 years, and 6.2% annually in men aged 70 years and older. American Indian/Alaska Native, Asian American/Pacific Islander, and Hispanic men are less likely than Black and White men to be diagnosed with localized disease (64%–67% vs. 71%–72%). Compared with White men, American Indian/Alaska Native men have 12% higher prostate cancer mortality despite 13% lower incidence, whereas Black men have double the prostate cancer mortality, with 67% higher incidence. In summary, continued increases in the diagnosis of advanced prostate cancer and persistent racial disparities underscore the need for redoubled efforts to optimize early detection while limiting overdiagnosis and to understand and address barriers to equitable outcomes.